Design of cement plant waste heat recovery generation - Bayuaji, R. (Institute of Electrical and Electronics Engineers Inc., 2015)
Waste heat in cement plant is a huge waste heat from kiln and raw mill plant. Such as ordinary power plant, waste heat recovery generation consist of various operation units ie., economizer, evaporator, super heater, steam drum, and turbine. In order to obtain the optimal heat recovery, proper operation units should be designed and arranged optimally. This paper describes heat recovery unit operations modelling using Aspen HYSYS software. Hysys can be utilized as single tool for design and simulate WHRG system. The steady-state and dynamic process simulation, simulate pinch analysis result, area of heat transfer and roughly cost-estimation could be provided using this tool. The results show the Aspen HYSYS model could provide satisfied engineering design data that could be used in construction stage. Â© 2015 IEEE.